The Strategic Imperative of Treasury and Financial Risk Management in a Volatile Economic Landscape - Purwanti, Dian (Advances in Management & Financial Reporting, 2023)
Purpose: This study explores the significance of treasury and financial risk management in volatile economic environments. It aims to assess the effectiveness of various risk mitigation strategies in enhancing financial stability and organizational resilience. The research hypothesizes that a well-integrated risk management framework can mitigate market uncertainties and improve long-term financial sustainability. Research Design and Methodology: The study adopts a qualitative literature review approach, systematically analyzing existing scholarly works to identify key themes, theoretical foundations, and practical insights related to financial risk management. The research synthesizes knowledge of financial, operational, and strategic risk management practices by reviewing various academic sources. Findings and Discussion: The findings highlight the critical role of structured risk management practices in maintaining financial stability, ensuring operational continuity, and strengthening competitive advantage. The study underscores the importance of integrating insights from recent research to develop adaptive risk management strategies that address financial risks holistically. Implications: The study suggests that organizations should foster a proactive risk-aware culture, leverage emerging financial technologies, and continuously align strategies with evolving regulatory requirements. Future research should explore the intersection of digital transformation and financial risk management to enhance predictive capabilities and decision-making processes in uncertain economic landscapes.